Comparative Efficacy of Intravenous Ciprofloxacin against Ceftriaxone in Spontaneous Bacterial Peritonitis Patients : Intravenous Ciprofloxacin Against Ceftriaxone in Spontaneous - Sheikh, Muhammad Imran; Yaqub, Muhammad Usman; Saeed, Farhan; Maqsood, Asim; Raza, Muhammad Asad (Pakistan Journal of Health Sciences, 2024)
Cirrhotic individuals with spontaneous bacterial peritonitis were treated empirically with ciprofloxacin or ceftriaxone. Objective: To compare the effectiveness of intravenous ciprofloxacin against ceftriaxone in cirrhotic patients who developed spontaneous bacterial peritonitis. Methods: This prospective interventional analysis was conducted at the Department of Medicine GHURKI Trust and Teaching Hospital, Lahore from Aug 2018 to 2023, and comprised 356 patients of spontaneous bacterial peritonitis. After getting informed written consent patients with ages 35-70 years were included. Equally divided cases into two groups, 178 patients in group I received intravenously ciprofloxacin 200mg and 178 patients in group II received intravenously ceftriaxone 1g for 6 days after every 12 hours. Post-treatment efficacy of both drugs was compared. Results: Patients under study had a mean age of 53.15 ± 11.67 years and had a body mass index of 24.8 ± 6.20 kg/m2. In group I efficacy was found in 142 (79.8%) and in group II effectiveness was found in 160 (89.9%) with p-value=0.002. We found a reduction in ascetic fluid polymorph nuclear count in both groups after 6 days with p<0.003. The frequency of complications in group II was higher found in 16 (8.9%) cases and in group I found in only 5 (2.8%) cases. 4 cases in group I and 2 cases in group II left against medical advice. The mortality rate was also non-significant among both groups. Conclusion: It was concluded that intravenous ciprofloxacin is equally efficacious as ceftriaxone in treating spontaneous bacterial peritonitis in cirrhotic individuals.